Mineralogical and geochemical characterisation of iron ore tailings and their potential to generate toxic elements At Khumani Mine - Mabunda, Nompumelelo (University of the Witwatersrand, Johannesburg, 2024)
Iron ore mining in South Africa has resulted in clearance of vast areas of land, large pits and volumes of waste material disposed as tailings dumps. Recently, poor management and compromised engineering of tailings dump in iron ore mines have led to incidences of wall failures, spilling tailings material over large areas of land. Inhabitants living near these mines often suffer injustices through contamination of water resources, dam siltation and soil contamination. Although many iron ore tailings dumps have been associated with generation of alkaline drainage, their contaminated footprints have been reported to contaminate groundwater aquifers. This research characterises the tailings material from the Khumani Iron Ore Mine through chemical and mineralogical analyses of leachable potential toxic elements using inductive coupled plasma spectrometry, mineralogical characteristics using x-ray diffraction, physicochemical properties, and acid base accounting. The study also investigates the interaction between tailings geochemistry and groundwater quality. Groundwater in the study is characterised by near neutral to alkaline pH with high concentrations of CaCO 3 owing to the geological formation of the area. The groundwater waters are classified as Ca–type in summer and as-non dominant in winter. Concentration of As (21.48±8.98 μg/l), Fe (22730.5±1827.57 μg/l), Mn (478.3±76.28 μg/l), Cu (60.8±4.34 μg/l), Zn (204.7±21.98 μg/l), Al (300.4±11.47 μg/l ,) Pb (65.7±6.9 μg/l ), Co (20.1±4.1 μg/l) and Ni (41.4±6.85 μg/l) exceed the permissible limits of the Department of Water Affairs and Forestry (1996) in winter but are compliant in summer owing to the increase in the water table and a dilution effect due to heavy rains. Tailings material contains high concentrations of Mn, Zn, B, Ni, Ba, Mo, Co, and Pb and relatively low concentrations of Cu, Cd, As, and Hg minerals in the tailings deposits which include quartz, haematite, magnetite, siderite, calcite, dolomite, K feldspar, plagioclase, talc, clinochlore, and anatase. Kaolinite minerals were shown to increase the adsorption sites for trace elements. Acid base accounting test classified the tailings material as non-acid producing with NP to AP ratio > 2. However, the high concentrations of PTEs, including Fe, Pb, and As, in the groundwater samples suggest that there is vertical movement of these elements iv from the tailings into the groundwater reserves. Therefore, the TSF material cannot be discarded in an unused pit without further treatment or lining to prevent contamination of groundwater resources.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment, School of Mining engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; potential toxic elements; iron ore; tailings dumps; groundwater; SDG-12: Responsible consumption and production